Chicken salami production by adding beef - Abdullah Keleş; Mustafa Atasever; Ahmet Güner; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the physical, chemical, microbiological and sensory properties of chicken salami produced by adding different proportions [0 (control), 10, 20 and 30 %] ol beel. Experimental production was repeated three times. Physical, chemical and microbiological properties of the samples were not differed significantly among the study. In sensory examinations, the samples of beef containing are more preferred than the chicken samples. As a result, it was concluded that 20 % and 30 % of beef addition to chicken meat in the production of salami made good effects on the sensory properties of the samples. So chicken salami consumption can be increased by adding beef in the production.